The Notary's Position in Making Credit Agreements for the Provision of Credit Facilities by Banks (Study of Batam Court Decision Number 36/Pdt. G/2021/PN Btm) - Immi Ira Monalisa Saragih; Dave Jehuda Hutama; Edrick Manuel Gunadi; Radot Marulitua Sihaloho; Surya Wardhana; Yudis Fajar Damanik (PT FORMOSA CENDEKIA GLOBAL, 2023)
In the midst of globalization and rapid economic growth. In an increasingly competitive business environment, business actors must continue to strengthen capital and business financing, and one method commonly used is through credit loans from financial institutions, such as banks. The role of banks and financial institutions as providers of capital has important implications in supporting economic growth and corporate activity. They act as intermediaries between public funds and borrowers, and participate in the implementation of national development, which involves economic equality, economic growth and national stability. In the legal context, credit agreements have a very important meaning in regulating the relationship between creditors (banks) and debtors (borrowers). The role of the Notary as a public official in drafting credit agreement deeds is to ensure that the agreement complies with legal provisions, applies fairly to all parties involved, However, the problems in credit agreements arise Batam District Court Decision Case Number 36/Pdt.G/2021/PN Btm discusses a situation where credit guarantees in the form of land certificates face serious obstacles. The cause was an internal blockade carried out by the National Land Agency, which resulted in the Notary being unable to bind the guarantee with a mortgage right. Through this case study, this article provides valuable insight into legal issues that may arise in banking credit practices in Indonesia